The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1242/jeb.01879
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial urate transport by avian renal proximal tubule epithelium in primary culture

Abstract: SUMMARY Birds are uricotelic, and because they excrete urate by renal tubular secretion, they provide a convenient model for examination of this process. Primary monolayer cultures of the isolated renal proximal tubule epithelium from the domestic chicken, Gallus gallus L., were mounted in Ussing chambers where several substrates/inhibitors of renal organic anion transporters were tested for the sidedness and specificity of their effects on transepithelial urate transport. Transepithelial electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
(75 reference statements)
0
31
0
Order By: Relevance
“…Since the mammalian kidney is influenced by the uricosuric effects of DF and MLX through the inhibition of the epithelial cell's basolateral UA-excreting organic anionic transporters (OATs) (also referred to as a PAH transporter), multi-drug resistance protein (MRP) and the apical UA reabsorptive channel known as URAT1, it is possible that a similar effect occurs in the vulture. The latter is plausible as similar PAH and MRP channels are involved with UA excretion in the chicken (birds do not reabsorbed UA) (Khamdang et al, 2002, Rafey et al, 2003, Dudas et al, 2005, Enomoto and Endou, 2005and Mount et al, 2006. In addition both diclofenac and phenylbutazone have been shown to induce uricemia in the chicken (Berger et al, 1960 andNaidoo et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Since the mammalian kidney is influenced by the uricosuric effects of DF and MLX through the inhibition of the epithelial cell's basolateral UA-excreting organic anionic transporters (OATs) (also referred to as a PAH transporter), multi-drug resistance protein (MRP) and the apical UA reabsorptive channel known as URAT1, it is possible that a similar effect occurs in the vulture. The latter is plausible as similar PAH and MRP channels are involved with UA excretion in the chicken (birds do not reabsorbed UA) (Khamdang et al, 2002, Rafey et al, 2003, Dudas et al, 2005, Enomoto and Endou, 2005and Mount et al, 2006. In addition both diclofenac and phenylbutazone have been shown to induce uricemia in the chicken (Berger et al, 1960 andNaidoo et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Urate is the major nitrogenous waste in birds, and, unlike in great apes (21), there is no significant facilitated reabsorption of urate detected in the perfused chicken renal proximal tubule (9) or in primary monolayer cultures of chicken renal proximal tubule epithelial cells (cPTCs) (13), only active secretion. URAT1 is believed by many to be the main contributor to urate reabsorption in humans; however, no similar sequence is present in the chicken genome, consistent with the lack of reabsorption in the avian system.…”
mentioning
confidence: 99%
“…Urate secretion has been directly measured in the perfused renal proximal tubule of adult chicken (9). Our previous characterization study of renal proximal tubule monolayer cultures from the neonate chicken indicated equivalent transport and inhibitor effects as seen in the adult perfused tubule (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured chicken proximal tubules, RT-PCR revealed mRNA for MRP2-and MRP4-like organic anion transporters in avian proximal epithelium. Luminal application of MK-571 (a known substrate for MRP2 and MRP4) dramatically reduced both uric acid secretory and re-absorptive flux (Dudas et al 2005). …”
Section: Multidrug Resistance Proteins (Mrps Abccs)mentioning
confidence: 99%